The Fibrolaparoscopy in diagnosis of hepatobiliary disease - Piñeyro, Alberto; Piñeyro, Luis (Cirugía del Uruguay, 1981)
Laparoscopy is most useful in diagnosis of hepatobiliary disease. It is a dependable procedure for diagnosis of a hepatopathy and is considered a valuable auxiliary well worth utilizing in gallbladder disease and jaundice.